Intestinal Alkaline Phosphatase Combined with Voluntary Physical Activity Alleviates Experimental Colitis in Obese Mice. Involvement of Oxidative Stress, Myokines, Adipokines and Proinflammatory Biomarkers - Aleksandra Danielak; Dagmara Wojcik; Agnieszka Mazur-Bialy; Marcin Surmiak; Jan Bilski; Aneta Targosz; Marcin Magierowski; Anna Chmura; Malgorzata Strzalka; Gracjana Krzysiek-Maczka; Katarzyna Magierowska; Urszula Szczyrk; et al. (MDPI AG, 2021)
Intestinal alkaline phosphatase (IAP) is an essential mucosal defense factor involved in the process of maintenance of gut homeostasis. We determined the effect of moderate exercise (voluntary wheel running) with or without treatment with IAP on the course of experimental murine 2,4,6-trinitrobenzenesulfonic acid (TNBS) colitis by assessing disease activity index (DAI), colonic blood flow (CBF), plasma myokine irisin levels and the colonic and adipose tissue expression of proinflammatory cytokines, markers of oxidative stress (SOD2, GPx) and adipokines in mice fed a standard diet (SD) or high-fat diet (HFD). Macroscopic and microscopic colitis in sedentary SD mice was accompanied by a significant decrease in CBF, and a significant increase in the colonic expression of tumor necrosis factor-alpha (TNF-α), IL-6, IL-1β and leptin mRNAs and decrease in the mRNA expression of adiponectin. These effects were aggravated in sedentary HFD mice but reduced in exercising animals, potentiated by concomitant treatment with IAP, especially in obese mice. Exercising HFD mice demonstrated a substantial increase in the mRNA for adiponectin and a decrease in mRNA leptin expression in intestinal mucosa and mesenteric fat as compared to sedentary animals. The expression of SOD2 and GPx mRNAs was significantly decreased in adipose tissue in HFD mice, but these effects were reversed in exercising mice with IAP administration. Our study shows for the first time that the combination of voluntary exercise and oral IAP treatment synergistically favored healing of intestinal inflammation, strengthened the antioxidant defense and ameliorated the course of experimental colitis; thus, IAP may represent a novel adjuvant therapy to alleviate inflammatory bowel disease (IBD) in humans.